The carbon count of 2000 years of rice cultivation. (30th December 2012) - Kalbitz, Karsten; Kaiser, Klaus; Fiedler, Sabine; Kölbl, Angelika; Amelung, Wulf; Bräuer, Tino; Cao, Zhihong; Don, Axel; Grootes, Piet; Jahn, Reinhold; Schwark, Lorenz; Vogelsang, Vanessa; et al.
Abstract: More than 50% of the world's population feeds on rice. Soils used for rice production are mostly managed under submerged conditions (paddy soils). This management, which favors carbon sequestration, potentially decouples surface from subsurface carbon cycling. The objective of this study was to elucidate the long‐term rates of carbon accrual in surface and subsurface soil horizons relative to those of soils under nonpaddy management. We assessed changes in total soil organic as well as of inorganic carbon stocks along a 2000‐year chronosequence of soils under paddy and adjacent nonpaddy management in the Yangtze delta, China. The initial organic carbon accumulation phase lasts much longer and is more intensive than previously assumed, e.g., by the Intergovernmental Panel on Climate Change (IPCC). Paddy topsoils accumulated 170–178 kg organic carbon ha −1  a −1 in the first 300 years; subsoils lost 29–84 kg organic carbon ha −1  a −1 during this period of time. Subsoil carbon losses were largest during the first 50 years after land embankment and again large beyond 700 years of cultivation, due to inorganic carbonate weathering and the lack of organic carbon replenishment. Carbon losses in subsoils may therefore offset soil carbon gains or losses in the surface soils. We strongly recommend including subsoils into global carbon accounting schemes, particularly for paddy fields.